An оptimisation рroblem of сhemically аctive substances concentration in gear oils - Захарченко, А.В. (Proceedings of National Aviation University (archive), 2005)
The ways to resolve an optimisation problem of the chemically active substances concentration as additives composition to technical oils are suggested on the basis of analytical review of contemporary tribology sources. The requirements to determine optimal concentration of additives composition in gear oils have been systematized.